El lavado de activos o blanqueo de capitales, su desarrollo normativo en el ámbito supranacional, su lesividad y su relación con el ordenamiento jurídico ecuatoriano - Angulo Gaona , Miguel Ángel (2017)
This essay pretends to analyze specific aspects of money laundering. The advance of the international regime on this behavior, at the same time, highlights what matters around this topic that has been discussed on every convention and it has also been developed with the purpose of filling existing legal, and political criminal vacuums left by previous conventions. Additionally, it pretends to give an explanation about the regulation progress that this crime has had in Ecuador. It also analyses the behavior legal terminology and its appropriate concept, which should be valued in the Ecuadorian legal system. Simultaneously, it presents a valuation of the different money laundering stages; by showing this process, we can analyze two important things: in the first place, how money laundering is generated from its origin until its illegal capital integration, and; in second place, by correctly observing this money laundering, we can identify which legal principle is the one that injures this activity.